Gambaran Penggunaan dan Penyimpanan Obat oleh Masyarakat di Kota Banjarmasin Tahun 2020 - Melviani Melviani; Onny Ziasti Fricilia; Jason Merari Peranginangin; Felix Imanuel Rachman; Munawarah Munawarah (Jurnal Surya Medika (JSM), 2021)
The COVID-19 pandemic has spread throughout the world, including in Banjarmasin, South Kalimantan. People use some medicines to maintain their health. This study aimed to describe the use of drugs in the community and their use and storage during a pandemic. This research method used an observational research design with a cross-sectional approach, using the convenience sampling technique with the google form application. The community-based survey was conducted on 101 respondents representing the community in Banjarmasin City for the general population group. The study results were 2 types of drugs that were widely used by respondents, namely vitamin drugs (72.3%) and supplements (27.7%). Respondents already know how to use drugs according to how they are used (83.2%), and the survey shows excellent results where (90.1%) of respondents take drugs as recommended by health workers. As many as (64.4%) of respondents knew how to store medicines according to their storage and (90.1%) store them properly. The conclusion is that the use and storage have a big impact on the quality of the drug, which currently the most popular are vitamin and symptomatic drugs.